2008
DOI: 10.1007/s00449-008-0215-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial sequencing of microbial reduction of chromate and nitrate in membrane bioreactor

Abstract: Sequential reduction of chromate and nitrate, two competitive electron acceptors, has been demonstrated for strains of Pseudomonas genus for both planktonic cells and cells immobilised in agar layers on the surface of synthetic membrane. Denitrification occurs practically after chromate depletion. This order of reduction process is consistent with redox potentials of the respective reactions. In a membrane bioreactor, competitive inhibition results in nitrate transfer through the membrane without transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
(18 reference statements)
0
6
0
1
Order By: Relevance
“…strain RCH2) from Hanford 100H . Although the correlation itself does not demonstrate that chromate reduction was cometabolic with nitrate reduction in the columns, it is clearly not what would be expected if nitrate and chromate were acting as competing electron acceptors used sequentially, as has been observed in other denitrifying cultures …”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…strain RCH2) from Hanford 100H . Although the correlation itself does not demonstrate that chromate reduction was cometabolic with nitrate reduction in the columns, it is clearly not what would be expected if nitrate and chromate were acting as competing electron acceptors used sequentially, as has been observed in other denitrifying cultures …”
Section: Resultsmentioning
confidence: 77%
“…12 Although the correlation itself does not demonstrate that chromate reduction was cometabolic with nitrate reduction in the columns, it is clearly not what would be expected if nitrate and chromate were acting as competing electron acceptors used sequentially, as has been observed in other denitrifying cultures. 22 Of the six columns that were exposed to influent containing 7.5 mM sulfate, two effectively depleted the influent lactate (5 mM) and chromate (5 μM) consistently after day 40 (Figure 1C,D and Supporting Information, Figure S3A−D) and were thus much more efficient at chromate reduction than the denitrifying columns. These two columns produced acetate and propionate as lactate fermentation products; the ratio of propionate:acetate observed in these columns (averaging ∼1.65 over the first 200 days) was similar to the ratio of 2.0 observed for the fermentative isolate Pelosinus sp.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Earlier studies had reported that the simultaneous removal of chromate and nitrate was viable 8, 9 . However, Cr(VI) has toxic effect on microbial activity and more potential to obtain electron donor than nitrate, and the nitrate reduction could be restrained by high Cr(VI) concentration 3, 9, 10 . Compared with biofilm, activated sludge has higher biological activity 7, 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Electro bioremediation where efect of electric ield is observed on pollutant reduction has also been studied [19][20][21]. Nitrate reduction by biological means has been reported to be carried out in luidized expanded bed bioreactors [22], submerged membrane bioreactor [23], continuous low bioreactors [24] as well as packed bed reactor [25] with PVS tubes [26], alginate [27], K-Carrageenan [28] and microbial cellulose [29] as immobilization matrices. It could either be through assimilatory or dissimilatory pathway.…”
Section: Introductionmentioning
confidence: 99%